Scriptural reasoning: An expression of what it means to be a Faculty of Theology and Religion - Beyers, Jaco (HTS teologiese studies, 2018)
During 2017, the year of its centenary celebration, the Faculty of Theology at the University of Pretoria finalised the process to change its name to the Faculty of Theology and Religion. This indicates an inclusivity and accommodative policy for all to study at the faculty. However, what does it mean to become a faculty of theology and religion at a public university in 21st century South Africa? The consequences and implications have not been thought through completely. This article does not pretend to identify all consequences of a name change but wants to contribute to the conversation by suggesting that the concept of scriptural reasoning might be one practice to be implemented as a consequence. Scriptural reasoning at a faculty of Theology and Religion, which is part of a public university in the South African context, attests to the way in which the faculty perceives its own identity. The relation between theology, religion and a public university is discussed, indicating the possibilities of implementing scriptural reasoning.